Assessment of cyanobacteria (blue-green algae) and green algae as phycoremediation agent for heavy metals contaminant - Othman, Rashidi; shaharuddin, Ruhul izzati (2017)
Global threats of water pollution and water scarcity due to rapid development are facing serious challenges and hence it is imperative to explore means for sustainable ways of averting the consequences. The dual application of microalgae for phycoremediation and biomass production for value production like biofuels and fertilizers is a feasible alternative. The present investigation was attempted to reduce the heavy metals pollutant from the mixtures of artificial waste water samples using cyanobacteria (blue-green algae) and green algae. Cyanobacteria used in this research are Synechochoccus and Pseudanabaena, while the group of green algae are Chlorella vulgaris and Pandorina morum. The results revealed that both group of species were efficient and having a potential to reduce heavy metals (Cu, Cr, Al, Pb, Fe and Cr) except P. morum. Our results clearly indicated that Synechococcus are highly efficient for removal of Pb>Cr>Fe>Cu>Al>Cd respectively. The research were conducted by developing two phases which are algae culturing and phycoremediation model system. Cyanobacteria and green algae were cultivated in Bold’s Basal Medium (BBM) in optimum condition. The treatments were run at three concentration of heavy metals, 1mg/L, 2mg/L and 3mg/L for four weeks in the treatment room, which every week the samples were analyzed by Inductively Coupled Plasma (ICP). Amongst the selected algae, Synechococcus was a great candidate as good agent of heavy metals removal. The waste water treatment using cyanobacteria offer good system for phycoremediation of heavy metal pollutants before final discharge.